The Effect of Survey, Question, Read, Recite, Record, Reflect, And Review (SQ5R) Method on Students’ Reading Comprehension - Septiani, Silvia; Nirwanto, Rahmadi (Journal Of Foreign Language Learning and Teaching, 2025)
ABSTRACT Reading was a crucial skill for students, especially in understanding English language content. This study examined the impact of the Survey, Question, Read, Recite, Record, Reflect, and Review (SQ5R) method on students' reading comprehension at MTs Hidayatul Muhajirin Palangka Raya. The research employed a quantitative pre-experimental design using a one-group pre-test and post-test approach, involving 28 students in the experimental class who were selected through purposive sampling. Data were collected using multiple-choice pre- and post-tests. A Paired Sample t-test revealed a significant improvement in students' reading comprehension scores (p = 0.00 < 0.05), with a t-count of 2.934, which exceeded the t-table value of 1.703. These results led to the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (Ha), indicating that the SQ5R method had a measurable effect on student performance. The findings suggested that SQ5R significantly enhanced reading comprehension and served as an effective instructional strategy. The study concluded that applying the SQ5R method positively influenced students’ ability to understand and analyze texts, making it a beneficial tool for improving reading skills during the 2024/2025 academic year. Keywords: Effect, Reading Comprehension, SQ5R Method, Students' Achievement